Study of lactose–fermenting yeasts kluyveromyces lactis for whey and apple pectin mixture fermentation - Chepel, Natalia; Grek, Olena; Krasulya, Olena (Eastern-European Journal of Enterprise Technologies, 2016)
This study was carried out by using whey and apple pectin in the fiber mixture as a fermentative medium in order to evaluate the biochemical activity of lactose–fermenting of some Kluyveromyces lactis strains during fermentation. The fermentation medium contained whey and apple pectin in the fiber in the ratio 9:1. Ten lactose–fermenting Kluyveromyces lactis strains coded 42 K, 95, 300, 304,317, 318, 325, 469, 868–K and 2452 were investigated. During cultivation in aerobic conditions the biomass yield was the highest by yeast cultivation in whey and apple pectin in the fiber mixture with Kluyveromyces lactis 868–K strain (71.3˟106 CFU/ml). Maximum biomass accumulation of Kluyveromyces lactis 868–K strain was achieved on the 30 h of cultivation at a temperature of 30±2° С. But the addition of apple pectin in the fiber into whey caused lactose–fermenting yeast growth inhibition (in exponential multiplication phase 1.59 % less biomass accumulation compared with the sample without apple pectin in the fiber). During the alcoholic fermentation, the dynamics of CO2 accumulation is positively correlated with the dynamics of biomass accumulation. Maximum CO2 content and ethanol content were observed after 30 h of fermentation at an optimal temperature of 32° С. The best contents of higher alcohols, aldehydes and esters were obtained in whey and APF fermented beverage by using Kluyveromyces lactis 868–K strain which consists of low contents of n–propane (1.84 mg/l), isobutane (29.30 mg/l), acetaldehyde (27 mg/l), and high contents of 2–methyl–1–butanol (73.52 mg/l), 3–methyl–1–butanol (211.11 mg/l), methylacetate (10.61 mg/l) and ethylacetate (85.11 mg/l).